Parallel reduction in flowering time from de novo mutations enable evolutionary rescue in colonizing lineages - Fulgione, Andrea; Neto, Celia; Elfarargi, Ahmed F.; Tergemina, Emmanuel; Ansari, Shifa; Göktay, Mehmet; Dinis, Herculano; Döring, Nina; Flood, Padraic J.; Rodriguez-Pacheco, Sofia; Walden, Nora; Koch, Marcus; et al. (Nature Communications, 2022)
Understanding how populations adapt to abrupt environmental change is necessary to predict responses to future challenges, but identifying specific adaptive variants, quantifying their responses to selection and reconstructing their detailed histories is challenging in natural populations. Here, we use Arabidopsis from the Cape Verde Islands as a model to investigate the mechanisms of adaptation after a sudden shift to a more arid climate. We find genome-wide evidence of adaptation after a multivariate change in selection pressures. In particular, time to flowering is reduced in parallel across islands, substantially increasing fitness. This change is mediated by convergent de novo loss of function of two core flowering time genes: FRI on one island and FLC on the other. Evolutionary reconstructions reveal a case where expansion of the new populations coincided with the emergence and proliferation of these variants, consistent with models of rapid adaptation and evolutionary rescue. Detailing how populations adapted to environmental change is needed to predict future responses, but identifying adaptive variants and detailing their fitness effects is rare. Here, the authors show that parallel loss of FRI and FLC function reduces time to flowering and drives adaptation in a drought prone environment.
Gesehen am 23.01.2023